2017
DOI: 10.1109/lmwc.2017.2751301
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of Motion-Induced Phase Errors in TDM MIMO Radars

Abstract: For high-resolution direction of arrival estimation, a wide aperture is necessary. This can be achieved with multipleinput multiple-output (MIMO) radars, which offer a wide virtual aperture. However, the requirement of orthogonal transmit signals has to be satisfied for their operation. Although time division multiplexing (TDM) of the transmit elements is an orthogonality realization with low hardware effort, phase errors occur in nonstationary scenarios. This work briefly discusses the problem of the motion-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…This error is usually either neglected for small velocities or is compensated by a double or overlapping element in the virtual aperture [39]. In [40] it is shown that such an overlapping element is not required and that the motion compensation can be resolved with smart signal processing. For frequency-division multiplexing the transmit antennas are 15 active at the same time but at different centre frequencies.…”
Section: Increasing Angular Resolution: Application Of Mimomentioning
confidence: 99%
“…This error is usually either neglected for small velocities or is compensated by a double or overlapping element in the virtual aperture [39]. In [40] it is shown that such an overlapping element is not required and that the motion compensation can be resolved with smart signal processing. For frequency-division multiplexing the transmit antennas are 15 active at the same time but at different centre frequencies.…”
Section: Increasing Angular Resolution: Application Of Mimomentioning
confidence: 99%
“…This reduces the maximum detectable Doppler frequency f D,max by the number of transmit antennas because the Doppler frequency f D is only sampled by every 8th transmitted ramp [27]. Furthermore, an additional phase difference of ∆φ TDM =2πf D T r due to the switching time occurs, which is corrected by an adapted discrete Fourier transform as in [34]. The time T r denotes the ramp repetition time between two consecutive ramp segments.…”
Section: Time-division Multiplexingmentioning
confidence: 99%
“…Its three transmitters and eight receivers form a uniform linear array with λ 2 spacing without overlapping virtual elements. The motion-induced phase error which leads to errors in the DoA estimation is compensated as described in [14]. The TDM usually reduces the maximum unambiguous velocity, which is restored by evaluating the phase trend along the virtual aperture as described in [15].…”
Section: Measurement Data Characteristicsmentioning
confidence: 99%